PENGARUH STORE ATHMOSPHERE DAN BRAND AWERENESS TERHADAP MINAT BELI ULANG KONSUMEN PADA WARUNG KOPI 88 BANJAR INDAH PERMAI MELALUI KEPUASAN KONSUMEN - Isra Ul Huda; Anthonius Karsudjono; Ryan Darmawan (Kresna Bina Insan Prima, 2020)
This study aims to determine and analyze the effect of Store Athmosphere and Brand Awereness Influence on Consumer Repurchase Interests at 88 Banjar Indah Permai Coffee Shop Through Consumer Satisfaction. This study uses quantitative data analysis methods, the analysis technique is Partial Least Square (PLS). The reason for choosing to use the PLS method is the testing of the mediating role of an intervening variable. The results of the analysis carried out stated that the Store Athmosphere had no significant effect on customer satisfaction and also repurchase interest. Brand Awereness has a significant effect on customer satisfaction and repurchase intention and Consumer satisfaction has a significant effect on repurchase interest. Store Athmosphere has no significant effect on repurchase intention through customer satisfaction while Brand Awereness has a significant effect on repurchase interest through customer satisfaction